A rare case of recurrent hyperparathyroidism. (27th January 2023) - Merugu, Chandhana; Naik, Dukhabhandu; Sahoo, Jayaprakash; Kamalanathan, Sadishkumar; Roy, Ayan; Narayanan, Niya; Patel, Deepika
Abstract:  : A 58 year old man presented to our hospital three years ago with history of upper abdominal pain, recurrent vomiting and dehydration. On evaluation, pancreatitis with mass in the head of pancreas was diagnosed. Fine needle aspiration from pancreatic head mass was suggestive of low-grade adenocarcinoma. Whipple's procedure was planned and the surgical gastroenterology team did open pylorus resecting pancreatoduodenectomy and feeding jejunostomy for him in October 2016. But the biopsy was reported as chronic calcific pancreatitis. On workup, hypercalcemia (12.5 mg/dl) was noted and hyperparathyroidism due to right inferior parathyroid adenoma was diagnosed as PTH levels were elevated (iPTH-474 pg/ml). He had a slippage of the jejunostomy tube and was readmitted. Right inferior parathyroidectomy was done by the surgical oncologist along with the repair of slipped feeding jejunostomy tube by the surgical gastroenterology team in the same sitting in March 2017. Biopsy was reported as right inferior parathyroid adenoma. Post-surgery, he had hungry bone syndrome which stabilized after one month. After 6 months, he started noticing a small nodule in the right side of the neck which progressively increased in size from a small nodule to a size of 1*1 cm over a duration of one year, associated with multiple small nodules superiorly. He also complained of weight loss, constipation, generalized weakness, and bone pains. Hypercalcemia was noted and iPTH level was again elevated (564.7 pg/ml). He was admitted for evaluation for recurrence of parathyroid adenoma/ parathyroid carcinoma/ parathyromatosis. Ultrasonography of the neck showed a 4*3 mm hypoechoic lesion with internal vascularity noted posterior to right lobe of thyroid and medial to great vessels, and multiple heterogenous hypoechoic well-defined lesions noted in the subcutaneous plane on the right side of the neck, few noted along surface of right strap muscle and sternocleidomastoid muscle. FNAC of the subcutaneous nodule was suggestive of parathyroid adenoma. Parathyroid scan showed multiple MIBI-avid nodule seen anterior and lateral to inferior pole of thyroid gland. He was operated in February 2019 and five nodules were removed. Biopsy was suggestive of parathyroid carcinoma. After the surgery, his symptoms improved but Calcium(13mg/dl) and iPTH (453 pg/ml) levels were elevated at 3 months follow up. Biopsy was suggestive of parathyroid carcinoma. But in view of the previous surgery, earlier biopsy report of adenoma and no metastasis, he was diagnosed to have parathyromatosis. A follow up CT revealed residual nodules in the neck. A repeat surgery was done in August 2019 to remove the nodules as the patient complained of persistent generalized malaise and bone pains. Following surgery, his iPTH levels remained elevated (iPTH pre-op-492.4 pg/ml; post-op- 444.4 pg/ml). His symptoms improved mildly. He was started on medical management for hypercalcemia with Cinacalcet. Figure 1. Image of the neck of the patient showing multiple nodules.